PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN HOTEL SWISS BELINN SKA DI KOTA PEKANBARU - Heru Soendoro; Zulkarnain Zulkarnain; Deny Danar Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to analyze the effect of the marketing mix of services to the satisfaction and loyalty of consumers in Swiss Belinn SKA Hotel Pekanbaru. The instrument used for data collection are questionnaires. The population of this research is the entire Hotel Swiss customers Belinn SKA Pekanbaru known until 2013 amounts to 28.123 people. The sample in this research is the user services Hotel Swiss Belinn SKA Pekanbaru elected of 100 people. Data analysis techniques using Path Analysis with SPSS Software 17. Result of calculations indicate that the product has a direct influence is not significant and positive with respect to satisfaction. Price has a direct influence is not significant and negatively to satisfaction. Location has a significant direct influence on Satisfaction and positively. Promotion has a significant direct influence on satisfaction and positivel. People have a significant direct influence and positively to the satisfaction, the process has a direct influence is not significant and positive to the satisfaction. Physical Means, have a direct influence is not significant and positive to satisfaction. Service Marketing Mix have significant direct influence and positively to loyalty and satisfaction of having a significant direct influence and positive to loyalty.Keywords: service marketing mix, satisfaction, and loyalty